PH balance and lactic acid increase in the vitreous body of diabetes mellitus patients. (November 2019) - Mieno, Hiroki; Marunaka, Yoshinori; Inaba, Tohru; Kojima, Kentaro; Yoneda, Kazuhito; Nagata, Kenji; Sotozono, Chie
Abstract: Although there have been no previous reports on the pH of the human vitreous body, it has been highly theorized that it changes in patients with diabetes mellitus (DM). In humans, it is necessary to measure the vitreous pH in vitro, which is an important point that presents a major problem, as vitreous pH immediately changes when exposed to air. The purpose of this present study was to report our recent development of an in vitro method for measuring vitreous pH via the combination of 27-gauge (G) vitreous surgery and a blood gas analyzer, as well as our investigative findings on whether or not there is a difference of pH depending on the presence of diabetes mellitus (DM). This cross-sectional study involved 30 subjects [18 subjects without DM (DM-) and 12 subjects with DM (DM+)] with no previous history of ophthalmologic surgery. The DM+ group included 6 cases of proliferative diabetic retinopathy (PDR) and 6 cases of non-PDR (NPDR). The DM- Group was comprised of patients with a macular hole or idiopathic epiretinal membrane. The DM+ Group included patients not only with macular hole or idiopathic epiretinal membrane but also diabetic macular edema, however, patients with obvious vitreous hemorrhage were excluded. In all patients, a vitreous specimen was anaerobically obtained at the start of 27G pars plana vitrectomy, with a venous blood sample being collected immediately prior to surgery. Between the DM- and DM+ subjects, pH, partial pressure of carbon dioxide (pCO2), partial pressure of oxygen (pO2 ), K +, Na +, Ca 2+, Cl −, lactate, and glucose were compared. In the items in which a significant difference was found between DM- and DM+, the values between the PDR and NPDR cases were also compared. Our findings showed no significant difference in vitreous and venous-blood pH between the DM- and DM+ subjects. The vitreous biochemical data revealed that Ca 2+ significantly reduced and lactate and glucose significantly increased in DM+ compared to DM-. Thus, we compared Ca 2+, lactate, and glucose between the PDR and NPDR cases. Although glucose did not significantly change, Ca 2+ significantly decreased and lactate significantly increased in the PDR cases. The venous biochemical data revealed that only glucose significantly increased in DM+. The data in all investigated items was found to be significantly different between the vitreous and venous samples. Our findings revealed that lactate increases and Ca 2+ decreases in the vitreous body of DM patients, especially those with PDR, probably due to the increased production of lactic acid. However, although the production of lactic acid increased, the pH remained at a nearly constant value, thus suggesting that the human vitreous body has a high buffering capacity. Highlights: There have been no previous reports on the pH of the human vitreous body. We developed an in vitro method for measuring vitreous pH and biochemical data. Lactate increases and Ca 2+ decreases in the vitreous body of DM patients. pH remained at a nearly constant value, regardless of the presence of DM. The human vitreous body might have a high buffering capacity.